A mathematical model of one-dimensional motion of the spray liquid at the outlet of the water-foam nozzle - Kamlyuk Андрей; Maksimovich Дмитрий; Chan Дык Хоан; Karpenchuk Игорь (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
The mathematical model of a spray liquid was considered in article. The system of equations, which describes the movement of the jet of atomized liquid leaving the water-foam head model was obtained. Theoretically study on the main characteristics of the nozzle in the effectiveness of extinguishing were conducted.